Development of the Composition and Technology of Orally Dispersed Tablets Based on Ethylthiobenzimidazole Fumarate - I. D. Kasymov; A. V. Basevich; A. L. Marchenko; V. A. Vainshtein (Разработка и регистрация лекарственных средств)
Introduction. The article presents the results of the development of the composition and technology of orally dispersed tablets of ethylthiobenzimidazole fumarate – a new actoprotective and adaptogenic agent.Aim. Development and substantiation of the composition and technology of orally dispersed tablets based on ethylthiobenzimidazole fumarate.Materials and methods. The technological properties of tablet samples were studied according to the methods of the State Pharmacopoeia of the XIV edition using the PGR-10 tablet press (LLC "LabTools", Russia), TBH 125 TDP tablet hardness tester (ERWEKA GmbH, Germany), ZT 322 m tablet disintegration tester (ERWEKA GmbH, Germany), TAR 220 abrasion tester (ERWEKA GmbH, Germany).Results and discussion. As a result of the study, the composition of orally dispersed tablets based on a new substance – ethylthiobenzimidazole fumarate was developed and justified. As a justification, the data of the analysis of the technological properties of the substance and excipients, the results of a multifactorial experiment planned using the Minitab 17 program, as well as data on the strength characteristics of the tablets obtained and the dependence of the disintegration time of the tablets and their strength characteristics on the pressing pressure are given.Conclusion. Based on the results of the study, the optimal composition of orally dispersed tablets based on ethylthiobenzimidazole fumarate is proposed.